Termination Of Employment Due To Company Bankruptcy During Covid 19 - Suseno Diharja (International Asia Of Law and Money Laundering (IAML), 2022)
One of the consequences of the covid 19 pandemic is that many companies are forced to lay off their employees and terminate their employment. The issue is whether the company is allowed to terminate the employment relationship due to Covid-19 and whether the company can be prosecuted for not being able to carry out its obligations to its workers. The research method used is lie research by using secondary data in the form of primary legal materials, secondary legal materials and tertiary legal materials. Research is normative juridical and qualitative type of research adalan. In conclusion, the company can terminate the employment relationship during Covid-19 on the grounds of Overmacht, if the company can prove due to the Covid-19 pandemic that it is no longer able to carry out its obligations to workers/ laborers. Companies that are unable to fulfill their obligations to their workers can be declared bankrupt and the seized assets of the company are subsequently sold, auctioned for payment of the rights of workers who are prioritized for payment.